Інформаційно-психологічні війни і їх вплив на свідомість суспільства - Дихтярук, Уляна; Матіїшин, Людмила; Савчин, Надія-Соломія; Марковець, Олександр (Видавництво Львівської політехніки, 2019)
With the rapid development of computerization and information society, the problem of information warfare appears to be more urgent than ever, but it is increasingly emerging as a threat to the stability of society. Information technologies are present in almost all spheres of social life of each person, which significantly influenced the fact that more and more people become more dependent on information every day. That is why information technology has become one of the most powerful means of influencing the mass consciousness of the whole society.
Keywords: інформаційно-психологічна війна; суспільство; інформатизація; маніпуляції; «фейкова» інформація; інформаційний вплив